EDGAR ALLAN POE'S ARRIVAL AND ROOTS IN JAPAN: FROM TRANSLATION TO MASS PHENOMENON - Cid Lucas, Fernando (2019)
This paper will study the reception and acceptance of the stories and poems by the American writer Edgar Allan Poe. Furthermore, it will analyze how these works and himself have influenced Japanese popular culture, specifically in media such as manga, anime and videogames.